2021
DOI: 10.30574/gscarr.2021.6.3.0055
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, pharmacology and botanical aspects of Murraya Koenigii in the search for molecules with bioactive potential - A review

Abstract: The magical plant of Indian spice, Murraya koenigii(curry leaf) family Rutaceae grows throughout the Indian subcontinent. It is used in the treatment or prevention of many diseases including kidney stone, dysentery disorders, renal pain, stomach upsets & morning sickness. It is one of the main components of formulation in the traditional ayurvedic system of medicine since many centuaries. A scrutiny of literature reveals some notable pharmacological activities of plant. These include pharmacological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…From spectroscopic analysis, various chemical constituents including cyclomahanimbine, girinimbine, mahanimbinine, murrayanine, murrayacine, mahanimbicine, mahanimboline, mukanol, and murrayacinine have been isolated. Some carbazole alkaloids such as murrayazoline, murrayazolidine, murrayazolinine, curryanin, curryangin, and isomurrayazoline were present in the stem bark [23] …”
Section: Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…From spectroscopic analysis, various chemical constituents including cyclomahanimbine, girinimbine, mahanimbinine, murrayanine, murrayacine, mahanimbicine, mahanimboline, mukanol, and murrayacinine have been isolated. Some carbazole alkaloids such as murrayazoline, murrayazolidine, murrayazolinine, curryanin, curryangin, and isomurrayazoline were present in the stem bark [23] …”
Section: Phytochemicalsmentioning
confidence: 99%
“…Stem bark extract yielded mukeic acid and mukoeic acid, respectively. The bioactive compounds with pharmacological activities are shown in Table 2, Table 3, [1–4,11,23–32] and (Figure 1).…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Curry trees also contain iron, Vitamins A, B, B2, and C, and were used as a calcium supply for people who needed it. Traditional uses for this plant include antifungal, antidepressant, anti-diarrheal, anti-inflammatory, and blood purifying properties, either in part or whole (53,54).…”
Section: Folk/traditional Usementioning
confidence: 99%
“…Several studies have demonstrated that plants enriched with polyphenols, including flavonoids, are interesting classes of bioactive phytochemicals that exhibit antimastitis/breast related infections, 22,23 preventing morning sickness 24,25 and vomiting during pregnancy. 26,27 Hence, E. aethiopicum is a source of numerous phytochemicals and polyphenols that possess antioxidant activities and traditionally possess the aforementioned activities, supporting the present study.…”
mentioning
confidence: 99%